2013
DOI: 10.4103/2231-0762.122439
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of relationship between body mass index and periodontal status among state government employees in Shimla, Himachal Pradesh

Abstract: Background:The literature shows that an increased body mass index (BMI) may be a potential risk factor for periodontitis. Association between BMI and periodontitis has been ascribed to unhealthy dietary patterns with insufficient micronutrients and excess sugar and fat content.Aim:The present study intended to assess the relation between BMI and periodontal status among state government employees in Shimla city, Himachal Pradesh in India.Materials and Methods:The study sample comprised 1,008 subjects aged 18-5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 12 publications
(15 reference statements)
0
8
2
Order By: Relevance
“…The odds ratio for BMI was 1.881 (95% CI 1.050-3.371) slightly higher than a previous study where OR was 1.56 (95% CI 1.26-1.92). 26 This finding was contrary to a study in Korea by Kim et al who with multivariate analysis found no association between BMI and periodontitis with BMI ≥ 25, adjusted ratio 0.991 (95% CI 0.806-1.220) but found a significant association between abdominal obesity and periodontitis with an adjusted odds ratio of 1.358 (95% CI 1.003-1.839). 14 Associations between obesity and periodontitis were found more consistently for visceral than general adiposity, suggesting that visceral fat accumulation measurement may be more strongly associated with periodontitis more than BMI.…”
Section: Abbreviationscontrasting
confidence: 66%
See 1 more Smart Citation
“…The odds ratio for BMI was 1.881 (95% CI 1.050-3.371) slightly higher than a previous study where OR was 1.56 (95% CI 1.26-1.92). 26 This finding was contrary to a study in Korea by Kim et al who with multivariate analysis found no association between BMI and periodontitis with BMI ≥ 25, adjusted ratio 0.991 (95% CI 0.806-1.220) but found a significant association between abdominal obesity and periodontitis with an adjusted odds ratio of 1.358 (95% CI 1.003-1.839). 14 Associations between obesity and periodontitis were found more consistently for visceral than general adiposity, suggesting that visceral fat accumulation measurement may be more strongly associated with periodontitis more than BMI.…”
Section: Abbreviationscontrasting
confidence: 66%
“…This data was in agreement with previous studies among the population aged 28-55 11 and among adults aged 18 to 24 years. 26 The clinical parameters of periodontitis (PD, CAL, recession and BOP) presented positive correlations with BMI (p < 0.05). This finding was in line with Zimmermann et al , a German population cohort study which also found an increased deeper periodontal pocket with higher BMI (OR = 1.6, BMI increase by 5).…”
Section: Discussionmentioning
confidence: 90%
“…Since then, several studies in adults have investigated a possible association between obesity and periodontitis [8][9][10][11][12][13][14][15][16][17][18][19]. A recent systematic review and meta-analysis included 28 independent studies done by Chaffee and Weston suggested positive association between periodontal disease and obesity across diverse populations with an OR of 1.35 (95% CI 1.23-1.47) whether BMI or waist circumference was used to define obesity [20].…”
Section: Introductionmentioning
confidence: 93%
“…Based on the results of previous studies [9][10][11][12][13][14][15][16][17][18][19][20][21], we hypothesise that obese women are more likely to have periodontitis than normal weight women.…”
Section: Introductionmentioning
confidence: 97%
“…Similar results were also observed in other studies done on Indian population. [21][22][23] In the study by Bhardwaj et al, 21 subjects had an increased risk of periodontitis by 56% for each 1 kg/m 2 increase in BMI, which means that a higher BMI could be a potential risk factor for periodontitis. Mathur et al 22 reported higher prevalence of periodontal disease in obese (88%) than in nonobese (74.4%) individuals (odds ratio = −20.4 and 95% CI 1.3-1.3).…”
Section: Jcdmentioning
confidence: 98%